Prevalence and Risk Factors Associated with Human Cytomegalovirus and Human Immunodeficiency Virus Coinfection in Pregnant Women in Ilorin, Nigeria - M. K., Olatunji; E., Oluwajana (Covenant Journal of Physical and Life Sciences, 2017)
Human Cytomegalovirus (HCMV) and Human Immunodeficiency (HIV) viral infection in pregnant patient is associated with high risk of maternal complications. This was a cross sectional study aimed to determine the prevalence and risk factors of HCMV and HIV mono-infections among 230 pregnant women attending ante-natal clinic of Sobi specialist hospital Ilorin, Nigeria. Data of consenting participant was collected via interviewer-administered questionnaire and clinical report form before collection of blood sample for analysis. The extracted serums were screened for HIV and CMV using rapid test-kits (Aleredetemine TMHIV1/2) and ELISA for detection of anti-CMV IgG and IgM respectively. All 230 participants were negative to HIV infection while 97.8% and 3.0% was CMV IgG and IgM positive respectively. High positivity was recorded across all age group with 15-19 having 100% anti-CMV IgG while the 25-29 and 30-34 years age group had highest anti-CMV IgM (P=0.907). 168(73.0%) of 171(74.3%) and 57(24.8%) of 59(25.7%) subjects within the parous and nulliparous group respectively were CMV-IgG positive while highest IgM positivity was noticed among the parous group (P=0.828). High CMV-IgG sero-positivity was also noticed across all level of education (P=0.700), marital status (P=0.668), types of marriage (P=0.008) and blood transfusion status (P=0.479). All the risk factors considered for HIV were very low while those for CMV had high sero-positivity for both current and past infections. The high level of CMV among pregnant women noticed in this study could be responsible for the congenital infection among newborns prevalent in the study area.